2017
DOI: 10.1007/s40262-017-0533-5
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Bayesian Estimators for Refined Dose Adjustment of a New Tacrolimus Formulation in Kidney and Liver Transplant Patients

Abstract: Population pharmacokinetic models and Bayesian estimators for Envarsus in kidney and liver transplantation were developed and are now available online for area under the curve-based tacrolimus dose adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 21 publications
3
58
2
1
Order By: Relevance
“…This underlines the usefulness of AUC estimation based on 3 observed concentrations and individual estimation of parameters using the Bayesian method (of note, VPC are based on population parameters and not individual parameters) in comparison to the C 0 . In a previous study, we found that the same structural model also accurately described the PK of Envarsus (another once‐daily formulation of TAC) in liver transplant recipients . Several other structural models were proposed to describe the PK of TAC OD and TD in liver transplant patients .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This underlines the usefulness of AUC estimation based on 3 observed concentrations and individual estimation of parameters using the Bayesian method (of note, VPC are based on population parameters and not individual parameters) in comparison to the C 0 . In a previous study, we found that the same structural model also accurately described the PK of Envarsus (another once‐daily formulation of TAC) in liver transplant recipients . Several other structural models were proposed to describe the PK of TAC OD and TD in liver transplant patients .…”
Section: Discussionmentioning
confidence: 96%
“…For TAC in liver transplant recipients, the LSSs described in the literature include sampling times up to a maximum of 4 h post dose, probably or explicitly because it is difficult to prolong patient stay at the hospital further for sample collection. However, this restriction could theoretically increase the bias and decrease the precision of AUC estimation for OD formulations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations